2015
DOI: 10.1002/app.42004
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐nanocomposite films based on cellulose nanocrystals filled polyvinyl alcohol/chitosan polymer blend

Abstract: Bio-nanocomposite films based on polyvinyl alcohol/chitosan (PVA/CS) polymeric blend and cellulose nanocrystals (CNC) were prepared by casting a homogenous and stable aqueous mixture of the three components. CNC used as nanoreinforcing agents were extracted at the nanometric scale from sugarcane bagasse via sulfuric acid hydrolysis; then they were characterized and successfully dispersed into a PVA/CS (50/50, w/w) blend to produce PVA/CS-CNC bio-nanocomposite films at different CNC contents (0.5, 2.5, 5 wt %).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 164 publications
(110 citation statements)
references
References 65 publications
8
91
0
11
Order By: Relevance
“…Figure 4, all extracted CNC samples exhibited lower Tonset and Tmax compared to other cellulosic materials (AW, ATAW and BAW). This finding was expected since various studies have shown that the insertion of sulfate groups, during sulfuric acid hydrolysis, lowers the thermal stability of CNC [24,26]. The presence of sulfate groups on the surface of the CNC has a catalytic effect in the thermal decomposition mechanism [32], which results in a reduced thermal stability for sulfuric acid hydrolyzed CNC.…”
Section: Thermogravimetric Analysis Of Cellulosic Materialsmentioning
confidence: 80%
See 4 more Smart Citations
“…Figure 4, all extracted CNC samples exhibited lower Tonset and Tmax compared to other cellulosic materials (AW, ATAW and BAW). This finding was expected since various studies have shown that the insertion of sulfate groups, during sulfuric acid hydrolysis, lowers the thermal stability of CNC [24,26]. The presence of sulfate groups on the surface of the CNC has a catalytic effect in the thermal decomposition mechanism [32], which results in a reduced thermal stability for sulfuric acid hydrolyzed CNC.…”
Section: Thermogravimetric Analysis Of Cellulosic Materialsmentioning
confidence: 80%
“…Additionally, the CrI increased from 66 % for bleached sample to 81, 83 and 87 % for 17 observations. Herein, the as-isolated CNC shows a high CrI (81-87%) compared with the CNC which were extracted from red algae (73%) [10], mulberry (73.4%) [46] , or sugarcane bagasse (77-65 %) [23,24].…”
Section: X-ray Diffraction Analysismentioning
confidence: 97%
See 3 more Smart Citations